THE INFLUENCE OF SOCIAL MEDIA MARKETING ON BRAND AWARENESS AND PURCHASE DECISIONS OF MILLENNIAL CONSUMERS - Haryantini, Haryantini (Yayasan Education and Social Center, 2025)
This study aims to analyze the influence of social media marketing on brand awareness and purchase decisions of millennial consumers. Using a quantitative approach with an explanatory research design, data was collected from 200 millennial respondents aged 27-43 years through an online questionnaire. The variables measured included social media marketing as an independent variable, brand awareness as a mediating variable, and purchase decisions as a dependent variable. Data analysis uses path analysis with SPSS version 26. The results showed that social media marketing had a positive and significant effect on brand awareness with a path coefficient of 0.672, explaining 45.2% variation. Social media marketing also has a direct effect on purchase decisions with a path coefficient of 0.387. Brand awareness has a significant effect on purchasing decisions with a path coefficient of 0.461. The mediation analysis showed that brand awareness played a role as a partial mediation variable with an indirect influence of 0.310 and a total influence of 0.697. Together, social media marketing and brand awareness explain 61.8% of millennial consumers' purchase decisions. This research provides theoretical contributions in enriching the digital marketing literature and practical implications for marketing practitioners in optimizing social media marketing strategies.